The Assessment of Serum Endocan Levels in Children With Juvenile Idiopathic Arthritis - Yasin YILMAZ; Rana BERRU DURMUŞ; Başak SARAÇOĞLU; Sezgin ŞAHİN and Amra ADROVIC and Kenan BARUT and Sevda ÖZEL YILDIZ and Özgür KASAPÇOPUR and Rukiye EKER ÖMEROĞLU (Archives of Rheumatology, 2018)
Objectives: This study aims to evaluate the levels of serum endocan in children with juvenile idiopathic arthritis (JIA). Patients and methods: Sixty-seven children with JIA (30 males, 37 females; mean age 10.4±4.9 years; range 2 to 18 years) and a sex- and age- matched healthy control group of 39 children (16 males, 23 females; mean age 9.3±4.1 years; range 1 to 17 years) were recruited. Patients with JIA were divided into two groups as the clinically active JIA group (n=27) and inactive JIA group (n=40). Results: The median serum endocan level in patients with JIA was significantly higher than in the control group (633.75 ng/L vs. 379.76 ng/L, p<0.01). Comparison between patients with active JIA and inactive JIA was not significant in terms of endocan levels (618.70 ng/L vs. 687.36 ng/L, p=0.34). There was a weak negative correlation between Childhood Health Assessment Questionnaire scores of patients with JIA and serum endocan levels. Conclusion: The high level of serum endocan highlighted the endothelial damage in patients with JIA.